GTRM-CoP Intersectionality conversation: Dimitra Clubs - What is the role of community engagement in gender-transformative change? - Monsieur, Christiane; Sanchez Enciso, Andrea; Bailey, Arwen (2024)
For many years, FAO has championed a community-driven approach centered on facilitating the engagement of rural communities—through dialogue and action—as catalysts for their own development. Known as Dimitra Clubs, this approach aims to promote rural people’s empowerment while enhancing women's leadership and gender equality. The Dimitra Clubs model is a powerful means for the Organization to deliver on the principles of “Leaving No One Behind” and “Gender Equality” in agrifood systems transformation.